Mediasi Organizational Citizenship Behavior Pada Pengaruh Kepemimpinan Instruksional Terhadap Kinerja Guru Sma/Smk Negeri Se-Kecamatan Jailolo - Onso, Tamsil La; Fahri, Johan; Jannang, Abdul Rahman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Abstract Teacher performance is an important variable that determines the success of schools in realizing a quality and quality educational process. However, the achievement of expected teacher performance according to educational demands cannot be separated from the principal's instructional leadership and organizational citizenship behavior (OCB) factors possessed by teachers. This study aims to examine the effect of instructional leadership on teacher performance mediated by OCB in public senior high schools (SMA/SMK) throughout Jailolo district, West Halmahera regency. This study uses a causality design with a quantitative research approach. The data in this study are primary data collected through distributing questionnaires to 75 senior high school (SMA/SMK) teachers throughout Jailolo district, West Halmahera regency. The data were then analyzed using the partial least squares-structural equation model (SEM-PLS) method with smartPLS4 software. The results showed that instructional leadership has a positive and significant effect on teacher performance, instructional leadership has a positive and significant effect on OCB, OCB has a positive and significant effect on teacher performance, and OCB is able to partially mediate the effect of instructional leadership on teacher performance in senior high schools (SMA/SMK) throughout Jailolo district, West Halmahera regency. Further research is expected to address the limitations of this study.